A BOOK REVIEW: A DEAFENING SILENCE?: THE MUTE ECHOING BACK - Dr.Judith Balares Salamat (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
"Batang-bata ka pa at marami ka panglKailangang malaman at intindihin sa mundo/Van ang totoolNagkakamali ka kung akala rno nalAng buhay ay isangmumunting paraiso lamang." Translation: You're still too young and you have a lot of things / to know and understand (about) the worldlfhis is the truthlYou're mistaken when you thinklLife is but a small paradise.) Thus runs a Filipino song entitled, "Batang-BatakaPa" (You're TooYoung"), sung by a famous '70s trio. Adults tell young ones that they have a lot to learn about the world and they are still too young to mind all the cares in the world. They're too young to know that unlike what they think, life is not a paradise